The Role of Moderation in Human Resource Competence in the Influence of Budget Planning and Implementation and Administrative Recording on Budget Absorption in the Government of Sragen Regency, Indonesia - Maryanti, Istinganah Eni (Open Access Indonesia Journal of Social Sciences, 2023)
HR competence moderation becomes an important element in understanding how HR influences budget absorption in the Sragen Regency Government. Moderation, in this context, refers to HR's role in controlling and facilitating the relationship between budget planning, budget execution, and administrative records. HR competence includes the ability of individuals to plan, implement and document budgets properly. This study aimed to determine the role of HR competence in moderating the influence of budget planning and implementation, as well as administrative records of budget absorption in the Government of Sragen Regency, Indonesia. This study shows that HR competence moderates the effect of budget planning on budget absorption. HR competence moderates the effect of administrative records on budget absorption.